Effects of avocado seed extract in different tris-extenders on sperm and oxidative stress parameters of West African Dwarf goat spermatozoa during vitrification - Daramola, James Ola; Onanuga, Oluwakemi Dayo; Abioja, Monsuru Oladimeji; Adeleke, Mathew; Olowofeso, Olajide; Oke, Oyegunle Emmanuel; Adekunle, Ezekiel Oluwafemi; Sorongbe, Taiwo Amidu; Iyanda, Olayinka Ayobami (Journal of Agricultural Sciences (Belgrade), 2016)
Abstract: Effects of avocado seed extract (ASE) in different tris-extenders on sperm and oxidative stress parameters of West African Dwarf (WAD) goat during vitrification were evaluated. Semen samples were diluted with different levels of ASE (0, 5, 10, 15 and 20 mL/100 mL of diluent) each in tris citric acid (TCA), tris sodium phosphate (TSP) and tris sodium citrate (TSC) extenders while Tris-extender without citric acid, sodium phosphate and sodium citrate served as control. Diluted semen samples were vitrified and stored for 30 days. The results showed higher (P